2014
DOI: 10.1161/atvbaha.114.303450
|View full text |Cite
|
Sign up to set email alerts
|

Gene Deletion of Protein Tyrosine Phosphatase 1B Protects Against Sepsis-Induced Cardiovascular Dysfunction and Mortality

Abstract: Objective-Cardiovascular dysfunction is a major cause of mortality in patients with sepsis. Recently, we showed that gene deletion or pharmacological inhibition of protein tyrosine phosphatase 1B (PTP1B) improves endothelial dysfunction and reduces the severity of experimental heart failure. However, the cardiovascular effect of PTP1B invalidation in sepsis is unknown. Thus, we explored the beneficial therapeutic effect of PTP1B gene deletion on lipopolysaccharide (LPS)-induced cardiovascular dysfunction, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…This suggested a direct role for PTP1B in the control of endothelial relaxation. A similar role for PTP1B has previously been suggested by the group of Vincent Richard who demonstrated that deletion or pharmacological inhibition of PTP1B prevented heart failure- or sepsis-induced endothelial dysfunction [ 10 , 23 ]. The authors of the latter studies argued for a direct beneficial effect of PTP1B inhibitors on endothelial function.…”
Section: Discussionsupporting
confidence: 59%
“…This suggested a direct role for PTP1B in the control of endothelial relaxation. A similar role for PTP1B has previously been suggested by the group of Vincent Richard who demonstrated that deletion or pharmacological inhibition of PTP1B prevented heart failure- or sepsis-induced endothelial dysfunction [ 10 , 23 ]. The authors of the latter studies argued for a direct beneficial effect of PTP1B inhibitors on endothelial function.…”
Section: Discussionsupporting
confidence: 59%
“…First, as suggested by convincing evidence that early endothelial dysfunction, and especially alteration of eNOS-mediated production of NO, plays a major role in endothelial dysfunction leading to cardiac dysfunction [41], we confirmed that induction of TMA decreased eNOS mRNA expression in cardiac ventricles. This unreported effect may be worsened by the widespread microthrombi that may be responsible for tissue hypoxia, which is known to decrease eNOS expression [42,43].…”
Section: Discussionsupporting
confidence: 78%
“…Protein tyrosine phosphatase 1B (PTP1B) plays a vital role in endoplasmic reticulum (ER) stress and is regarded as a potential target for therapeutic intervention in obesity‐induced cardiomyopathy (Kandadi et al, ) and septic shock‐induced cardiovascular dysfunction (Coquerel et al, ). Krishnan et al found that H 2 S induced PTP1B S‐sulfhydration at Cys 215 to inhibit its activity, which facilitated phosphorylation and activation of protein kinase‐like ER kinase, and promoted restoration of ER homeostasis.…”
Section: H2s Induced Protein S‐sulfhydrationmentioning
confidence: 99%